Handwriting validation: results and validity of comparison materials. Case discussion - Alămoreanu, Sorin; Florescu, Bogdan (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
In most cases “handwriting validation” is synonymous to “establishing the graphical structure’s author”. If this is absolutely true for the cases when handwriting samples have been created for the comparison purposes in the presence of the judicial organ, certain cases could come to the point where the presumed authors are deceased or missing, or the materials offered for judgment have been written on previous occasions also known as “free comparison samples”. Still, practice has proven the contrary to the perfect overlapping of the two expressions. In certain debates, the contradictorily phases of evidence admission comparison samples offered by one of the litigating parties are supposed to the accept acceptance or rejection of the other part. Notary procedures though usually have no debate over the source of the comparison materials, as they generally are presented by the inheritors. Therefore, there will be no contradictorily debate upon. Romanian handwriting examination practice has met certain situations when based on the uncontested initial origin of the comparison writing, experts have validated certain writing on documents in full honesty. After a certain time legal heirs have challenged in court those documents and the identification reports based upon them, offering a wider and more trusted range of writing and signatures from the supposed author. One can assume that in such cases even though the validation was formally correct, the true author of the handwriting has not been identified and the wrong premise of handwriting paternity has led to a an erred legal appearance, being generated as such through mistaken comparison samples.
Keywords: badanie pisma ręcznego; materiały porównawcze; ekspertyzy; ważność materiałów porównawczych